Capecitabine-induced hyperosmolar hyperglycaemic state. Issue 3 (24th March 2021) - Yim, Carly; Hussein, Nassrein; Arnason, Terra
Abstract : An elderly woman with metastatic breast cancer was admitted with hyperglycaemic hyperosmolar state (HHS) and an elevated haemoglobin A1C. For 1 week, she had experienced confusion, nausea and frequent urination. Preceding this, she had completed seven cycles of capecitabine chemotherapy for her breast cancer. She did not have a history of diabetes prior to chemotherapy. Given the temporal dysglycaemia following the patient's chemotherapy regimen, capecitabine was thought to be a probable offending agent. The patient was acutely treated for HHS, and was discharged on a basal-bolus insulin regimen. Her capecitabine was held pending review with her oncology team. The patient was ultimately titrated down to basal insulin only by her family doctor. Given the common use of capecitabine, it is important to recognise the risk of hyperglycaemic and hyperglycaemic emergencies as potential adverse effects. This highlights the need to monitor blood glucose throughout treatment to prevent hyperglycaemic emergencies.